Survival of the spirit : Tibet a decade of images (1998)
[Dt.:] Die Photografin und studierte Botanikerin Nancy Jo Johnson lebte vier Jahre in Nepal und engagiert sich für die Belange der im Exil und in der Himalajaregion lebenden Tibeter. In der Ausstellung "SURVIVAL OF THE SPIRIT, Tibet a Decade of Images", die Ende August 1998 in der Indigo Galerie in Kathmandu, Nepal, eröffnet wurde, wurden 25 ihrer Tibet-Photografien gezeigt. In der Online-Ausstellung werden elf dieser Bilder mit Erklärungstext veröffentlicht. Zudem werden Informationen zur Vita der Autorin bereitgestellt. - [Engl.:] The photographer Nancy Jo Johnson is trained as a botanist at the University of Wisconsin, doing her masters study in the Himalayas. She lived in Nepal for four years, working as a researcher and trek leader, and started her engagement for the local and exile Tibetans. The exhibition "SURVIVAL OF THE SPIRIT, Tibet a Decade of Images", shown in the Indigo Gallery, Kathmandu, Nepal, at the end of August 1998, is a culmination of 25 photographic images that records the conditions inside Tibet and of the Tibetan people in exile. The on-line version of this exhibtion provides eleven of these pictures and informs about the author Nancy Jo Johnson.